A péterváradi csata potosí krónikájában - Kukovecz György (University of Szeged, Magyar Medievisztikai Kutatócsoport Szeged, 1991)
The chronicle "Historia de la Villa Imperial de Potosí" by Bartolomé Arzáns de Orsúa y Vela (cc. 1676—1736) treats of the 1545 — 1736 history of Potosí. Though the chronicler deals mainly with the events of the life of the "silver town", there is considerable information concerning Hungary as well. The longest piece is the description of the battle of Pétervárad (August 5th, 1716) in the first Turkish war of German emperor Charles VI, who was king of Hungary as well, as Charles III. The chronicler's sources were the official Spanish statements. Arzáns's chronicle contributes to our knowledge about the kind of information about Hungary in the New World, and about the image of Hungary in the remote West Indies in the early 18th century.
Keywords: Bölcsészettudományok; Történettudomány és régészet